ETYMOLOGICAL CLASSIFICATION OF CLOTHING NAMES IN UZBEK AND ENGLISH LANGUAGES (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the etymological classification of clothing names in Uzbek and English languages. It analyzes the historical sources of clothing vocabulary, including native lexical layers and borrowings from Persian, Arabic, Russian, French, Latin, and other languages. The study reveals that clothing terminology reflects not only linguistic development but also cultural contacts, social transformation, and historical evolution. The comparative analysis shows that both languages demonstrate multilayered lexical systems shaped by cultural and global influences.
Keywords: Etymology, clothing names, Uzbek language, English language, borrowings, linguoculture, lexical layers.